2018
DOI: 10.3892/ol.2018.7751
|View full text |Cite
|
Sign up to set email alerts
|

Role of epithelial-mesenchymal transition markers E-cadherin, N-cadherin, β-catenin and ZEB2 in laryngeal squamous cell carcinoma

Abstract: Epithelial-mesenchymal transition (EMT) allows neoplastic cells to gain the invasive phenotype and become migratory, which is required for cancer progression and metastasis. In the present study, the expression of EMT-associated biomarkers and their association with clinicopathological parameters in laryngeal squamous cell carcinoma (LSCC) was investigated. E-cadherin, N-cadherin, β-catenin and zinc finger E-box binding homeobox 2 (ZEB2) protein expression was evaluated with immunohistochemistry in a cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 40 publications
4
50
0
1
Order By: Relevance
“…[15] Zhu et al in his systematic review reported that E-Cadherin could be a critical factor in predicting the prognosis of Laryngeal Squamous Cell Carcinoma (LSCC). [27] A downregulation in the E-Cadherin expression in patients with LSCC was reported by Nardi et al and signifies its prognostic importance in cervical metastasis. [28] A comparison of main characteristics of the studies included in literature review with the present study are highlighted in Table 3.…”
Section: Fig 2 Low Expression Of E-cadherinmentioning
confidence: 83%
“…[15] Zhu et al in his systematic review reported that E-Cadherin could be a critical factor in predicting the prognosis of Laryngeal Squamous Cell Carcinoma (LSCC). [27] A downregulation in the E-Cadherin expression in patients with LSCC was reported by Nardi et al and signifies its prognostic importance in cervical metastasis. [28] A comparison of main characteristics of the studies included in literature review with the present study are highlighted in Table 3.…”
Section: Fig 2 Low Expression Of E-cadherinmentioning
confidence: 83%
“…EMT serves a key role in the metastasis of LUAD . Tumor progression is often associated with the loss of E‐cadherin and β‐catenin, and an increase in the expression levels of vimentin and N‐cadherin, which result in more motile and invasive characteristics . To investigate the effect of lenti‐shACTL8 on E‐cadherin, β‐catenin, vimentin and N‐cadherin, A549 and NCI‐H1975 cells were infected with lenti‐shACTL8 for three days and evaluated by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…14 Tumor progression is often associated with the loss of E-cadherin and β-catenin, and an increase in the expression levels of vimentin and N-cadherin, which result in more motile and invasive characteristics. 15 To investigate the effect of lenti-shACTL8 on E-cadherin, β-catenin, vimentin and Ncadherin, A549 and NCI-H1975 cells were infected with lenti-shACTL8 for three days and evaluated by western blotting. It was revealed that shACTL8 significantly increased the expression level of N-cadherin and β-catenin, and decreased that of vimentin in A549 cells.…”
Section: Shrna Inhibition Of Actl8 Reduces Emt In Human Luad Cellsmentioning
confidence: 99%
“…Authors have shown that adhesion proteins like E-cadherin are actively involved in mesenchymal to epithelial (MET) and epithelial to mesenchymal (EMT) transitions, which play an important role in cancer progression and tissue fibrosis 48 . The current immunohistochemistry results from kidney sections showed that E-cadherin expression appeared lower in the FB group and higher in the naïve and BBT-059 administered groups at six months.…”
Section: Discussionmentioning
confidence: 99%